Modeling and ball speed validation of a new sepaktakraw ball launcher - Basyiruddin, Burhan; Mohd Nor, Mohad Anizu; Reduan, Mohd Sumali; Mohamad, Zulfakri; Ismail, Shariman Ismadi (Faculty of Sports Science and Recreation, 2025)
In recent years, the opponent's serve has become faster in sepaktakraw, resulting in the defensive work becoming a much harder task. Therefore, an effective training method to improve the defensive skills in sepaktakraw is imperative. Due to this reason, we have developed a new sepaktakraw ball launcher that can support sepaktakraw defence training. The aim of this study is to model and verify the ball’s speed launched from the device. The prototype ball launcher was developed based on a parametric model of the launcher mechanism and real-world sepaktakraw ball kinematics. The prototype ball launcher’s capability to launch sepaktakraw balls that reach real-world ball velocity was verified using a high-speed (480 Hz) camera motion analysis at four different launcher’s speed capacities (70%, 90%, 95% and 100%). The results showed that the launched ball speeds from the experiment were lower than the theoretical launched ball speed for all speed capacities, only reaching the maximum speed of 59.4 km/h at 100% speed capacity. It can also be observed that the differences between the experimental and the theoretical speeds were increased at higher motor speed capacities, indicating that lower motor efficiency could be one of the possible causes of the launcher producing low ball speeds during launch. Though the top speed of the launched ball was close enough to the real-world average ball speed during a serve (60 km/h), based on the launcher’s overall performance, further improvements are required before it is ready to be used for the training of elite athletes. Thus, several improvements to the ball launcher were suggested to increase the launched ball speed.